Adaptive Mechanisms Make Lupin a Choice Crop for Acidic Soils Affected by Aluminum Toxicity - Quiñones, Miguel A.; Lucas, M. Mercedes; Pueyo, José J. (Frontiers in Plant Science, 2022)
Almost half of the world’s agricultural soils are acidic, and most of them present significant levels of aluminum (Al) contamination, with Al3+ as the prevailing phytotoxic species. Lupin is a protein crop that is considered as an optimal alternative to soybean cultivation in cold climates. Lupins establish symbiosis with certain soil bacteria, collectively known as rhizobia, which are capable of fixing atmospheric nitrogen. Moreover, some lupin species, especially white lupin, form cluster roots, bottlebrush-like structures specialized in the mobilization and uptake of nutrients in poor soils. Cluster roots are also induced by Al toxicity. They exude phenolic compounds and organic acids that chelate Al to form non-phytotoxic complexes in the rhizosphere and inside the root cells, where Al complexes are accumulated in the vacuole. Lupins flourish in highly acidic soils where most crops, including other legumes, are unable to grow. Some lupin response mechanisms to Al toxicity are common to other plants, but lupin presents specific tolerance mechanisms, partly as a result of the formation of cluster roots. Al-induced lupin organic acid secretion differs from P-induced secretion, and organic acid transporters functions differ from those in other legumes. Additionally, symbiotic rhizobia can contribute to Al detoxification. After revising the existing knowledge on lupin distinct Al tolerance mechanisms, we conclude that further research is required to elucidate the specific organic acid secretion and Al accumulation mechanisms in this unique legume, but definitely, white lupin arises as a choice crop for cultivation in Al-rich acidic soils in temperate climate regions.